A case study on the experiences of persons with disabilities of the disability grant processes occurring at SASSA Springbok in the Northern Cape - Bock, Stacey Louisa (Department of Health and Rehabilitation Sciences, 2022)
Introduction: Persons with disabilities (PWDs) living in rural areas are known to have a higher risk of living in poverty as they have the lowest levels of employment. To assist persons with disabilities to overcome these challenges, the South African government has developed interventions such as social assistance programmes which aim to prevent poverty and assure the basic minimum standard of living. Over the past five years minimal research has been published which focused on the disability grant in the South African context. More specifically, no research has been conducted in the Northern Cape, home to a high proportion of persons with disabilities. Of the research conducted in other parts of South Africa, no studies have sought to understand the experiences of persons with disabilities while engaging in the disability grant process. The research question for this study was, “How are PWDs experiencing the disability grant processes occurring at the SASSA Springbok branch in the NC?” This study therefore aimed to describe the experiences of disabled persons with the disability grant processes as they occurred at the South African Social Security Agency (SASSA) in Springbok, Northern Cape. Method: A single instrumental case study research design was utilised. Five participants were purposively sampled. Data were collected through document review of pertinent SASSA documents, non-participant observation, and semi-structured interviews. Data were analysed inductively, taking a thematic approach. Findings: The theme that emerged was Respecting differences is part of humanity. The main findings reveal that engaging with persons with disabilities as humans and not disregarding their humanity because of their disability are imperative to how they experience the disability grant process. Two categories, For us, human dignity matters, and the Impact of context on occupational rights, encapsulate two specific areas that relate to the theme. Conclusion: The experience of the disability grant process in this case study was influenced by stakeholder engagement with participants, mandatory protocols implemented due to the novel coronavirus, and the administrative aspects of the process. Recommendations for an improved overall experience of the disability grant process include streamlining the disability grant application process, the implementation of consistent Batho Pele principles by all stakeholders, suitably accommodating the disability grant application process for all types of disabilities, as well as maintaining the logistical structures put in place (albeit unintentionally) from the year 2020.